Survival after cytoreductive surgery and hyperthermic intraperitoneal chemotherapy for colorectal peritoneal metastases: A systematic review and discussion of latest controversies. Issue 5 (October 2021) - Flood, Michael; Narasimhan, Vignesh; Waters, Peadar; Ramsay, Robert; Michael, Michael; Warrier, Satish; Heriot, Alexander
Abstract: Introduction: Peritoneal metastases confer the worst survival amongst all sites of metastatic colorectal cancer. The adoption of cytoreductive surgery (CRS) with hyperthermic intraperitoneal chemotherapy (HIPEC) has become an option for patients with isolated colorectal peritoneal metastases (CRPM). The aim of this study was to evaluate the outcomes following CRS and HIPEC for CRPM from published high volume cohort studies and to highlight the latest controversies and future directions of CRPM treatment. Materials and methods: A systematic review was performed on published studies on the treatment outcomes of CRS and HIPEC for colorectal peritoneal metastases. Results: Twenty studies met the inclusion criteria for the systematic review. The median survival for all patients ranged from 14.6 to 60.1 months. The 5-year overall survival ranged from 23.4% to 52%. For patients with complete cytoreduction, the median survival was 25 to 49 months. Major morbidity and mortality ranged from 15.1% to 47.2% and 0% to 4.5%, respectively. Conclusion: CRS and HIPEC for the treatment of CRPM is safe and current evidence suggests it improves both median and disease-free survival. However, the efficacy of intraperitoneal chemotherapy, in particular oxaliplatin, has recently come under scrutiny. Accordingly, higher quality evidence is urgently required to contribute to multidisciplinary and international consensus on CRPM treatment strategies. Highlights: Colorectal peritoneal metastases confer the worst overall survival amongst all sites. CRS and HIPEC can offer patients with these metastases favourable outcomes. Due to recent trials, the efficacy of HIPEC has come into question. Further high-quality evidence is required, in what remains a largely unexplored field.